Dinamika Audit Modern: Tinjauan Literatur tentang Kualitas Audit, Skeptisisme Auditor, Independensi, dan Konsekuensi Ekonomi dalam Era 2021–2025 (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to review the dynamics of modern auditing during the period 2021–2025 through a systematic literature review (SLR) approach to international studies that discuss audit quality, auditor independence, professional skepticism, and the economic consequences of audits. This study identified that audit quality is influenced by the interaction between internal factors—such as firm profitability, professional culture, and audit production design—with external factors such as regulation, market demand, and reputational pressure. Auditor independence remains a central issue, especially in the context of non-audit service delivery that raises a dilemma between objectivity and efficiency. Professional skepticism proves to be the primary protective mechanism in detecting material misrepresentation, while auditors' reputation contributes significantly to a decrease in the client's cost of capital. In the midst of digital transformation, auditors are faced with the demands of increasing technological competence and adjusting to risk-based regulations. Digitalization not only speeds up the audit process, but also expands expectations for transparency and accountability. These findings confirm that the future of auditing will be determined by the synergy between sustainable professionalism, adaptive regulation, and strategic use of technology. Thus, modern audits not only serve as a verification tool, but also as a strategic instrument in maintaining the integrity and credibility of global financial statements. This study makes a conceptual contribution to the development of audit policies and the establishment of standards of practice that are responsive to the dynamics of the contemporary business environment.